2021
DOI: 10.1186/s12992-021-00791-4
|View full text |Cite
|
Sign up to set email alerts
|

Universal coverage of the first antenatal care visit but poor continuity of care across the maternal and newborn health continuum among Nepalese women: analysis of levels and correlates

Abstract: Background Routine maternity care visits (MCVs) such as antenatal care (ANC), institutional delivery, and postnatal care (PNC) visits are crucial to utilisation of maternal and newborn health (MNH) interventions during pregnancy-postnatal period. In Nepal, however, not all women complete these routine MCVs. Therefore, this study examined the levels and correlates of (dis)continuity of MCVs across the antenatal-postnatal period. Methods We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
2
8
1
Order By: Relevance
“…It is also similar to studies done in a multi-county study in 49 and 28 countries including Africa [ 5 , 14 ]. The result was again supported by a study conducted in Nepal [ 48 ]. Studies in Pakistan and Cambodia also showed the same finding [ 8 , 53 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It is also similar to studies done in a multi-county study in 49 and 28 countries including Africa [ 5 , 14 ]. The result was again supported by a study conducted in Nepal [ 48 ]. Studies in Pakistan and Cambodia also showed the same finding [ 8 , 53 ].…”
Section: Discussionsupporting
confidence: 77%
“…Again the finding of this study was lower than a study conducted in Tanzania (53.81%) [ 42 ], Kenya (66.30%) [ 43 ], Uganda (48%) [ 44 ], Nigeria (38.1%) [ 34 ], Zambia (42.70%) [ 45 ], Guinea (74%) [ 46 ], and rural Gahna (38.1%) [ 47 ]. The finding was also lower as compared to a study conducted in 28 African countries (44%) [ 14 ] and studies conducted in different parts of Nepal which was ranged from 39 to 58% [ 12 , 13 , 48 ]. The possible reason for this difference may be due to the fact that the first three studies in Ethiopia were conducted in smaller sample sizes and time variation may be attributed to the difference.…”
Section: Discussioncontrasting
confidence: 73%
“…Continuum of care in maternal and neonatal service delivery is in uenced by diverse factors at various levels in India, Napal, Egypt, Uganda and Ethiopia [21,26,32,[34][35]. Economic status, ethnicity, education, gender, religion and social in-equalities are the major factors for utilisation MNH CoC services [34,36].…”
Section: Introductionmentioning
confidence: 99%
“…Place of residence, maternal age at childbirth, parity and women's exposure to mass media, and maternal health messages were the major factors for underutilisation of the services [34]. In Napal underutilisation or discontinuation of MNH CoC happened among women of disadvantaged ethnicities, low wealth status, illiterate, had high birth order, involved in agricultural sector, had unwanted last birth order and had poor awareness of health mother-groups [21]. In Egypt MNH CoC service utilisation affected by women's age, educational level of both partners, birth orders and exposure to mass media [32].…”
Section: Introductionmentioning
confidence: 99%
“…Routine ANC visits encourage women to take recommended interventions for healthy pregnancies and newborns and reduce adverse pregnancy outcomes. For example, evidence suggests that women who complete recommended ANC visits are more likely to give birth at a health facility and complete postnatal care (PNC) and give childbirth assisted by SBAs compared to a pregnant woman without ANC visits [ 17 , 18 ]. In addition, uptake of recommended ANC interventions requires better health facility readiness (e.g., provision of essential medicines, trained health workforces), delivery of interventions, and uptake by disadvantaged population groups [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%